2020
DOI: 10.1039/d0dt00419g
|View full text |Cite
|
Sign up to set email alerts
|

Tunable carbocation-based redox active ambiphilic ligands: synthesis, coordination and characterization

Abstract: Synthesis of carbenium-based ligands that are ambiphilic, redox active, and easily tunable along with their coordination to Co(ii) and Ni(ii).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…None of C≡C bonds present a strict linear arrangement; structures 4 c , 4 d , 4 f and 5 c displaying angles of 177.6°, 176.3° and 172.0° and 169.5° values respectively (Table 1, entry 3). For 4 c , 4 d and 4 f , the helicene core deformation was characterized by measuring both helical dihedral angles and helical pitch values (entries 4 and 5) which were not only similar among compounds 4 c , 4 d and 4 f but also with previously reported derivatives [4a,5k,6a,7a,10] …”
Section: Resultsmentioning
confidence: 72%
“…None of C≡C bonds present a strict linear arrangement; structures 4 c , 4 d , 4 f and 5 c displaying angles of 177.6°, 176.3° and 172.0° and 169.5° values respectively (Table 1, entry 3). For 4 c , 4 d and 4 f , the helicene core deformation was characterized by measuring both helical dihedral angles and helical pitch values (entries 4 and 5) which were not only similar among compounds 4 c , 4 d and 4 f but also with previously reported derivatives [4a,5k,6a,7a,10] …”
Section: Resultsmentioning
confidence: 72%
“…Instead, the carbenium ion is positioned to act as a Z-type ligand, [28][29][30][31][32] capable of interacting directly with the metal center through a M→C + interaction [33][34][35] as in complexes of type E[M]. 36 Interactions are also possible between the carbenium unit and metal-bound anionic ligands, as evoked by Gianetti for complexes of type F. 37 Because such -cationic phosphines are prone to phosphonium ion formation via "coordination" of the phosphorus atom to the carbenium center, 38 we have developed a strategy that provides direct access to the gold complexes [1-AuCl] + and [2-AuCl] + (Figure 1). 39 We found that these complexes efficiently catalyze reactions such as the cycloisomerization of propargyl amide without the addition of any activators.…”
Section: Introductionmentioning
confidence: 99%
“… 36 Interactions are also possible between the carbenium unit and metal-bound anionic ligands, as evoked by Gianetti for complexes of type F . 37 Because such γ-cationic phosphines are prone to phosphonium ion formation via “coordination” of the phosphorus atom to the carbenium center, 38 we have developed a strategy that provides direct access to the gold complexes [ 1 -AuCl] + and [ 2 -AuCl] + ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Not surprisingly, the barrier of racemization depends on size of the helical core (the larger the better) but also on the nature of the bridging heteroatoms and this property is, of course, not the only one being controlled by the dioxa, 15,19 azaoxa, 17,20 or diaza 14,16,21 nature of the compounds. 22 In fact, the modularity of the physical, electronic and chemical properties of these [4] and [6]helicenes 16,[23][24][25][26][27][28][29][30] depends also on the heteroatoms and this has led to many applications from biology 26,[31][32] to physics 33 but also in analytical sciences [34][35][36][37][38] and in (chir)optical spectroscopy. [39][40] Recently, late-stage regioselective functionalizations of compounds 3 and 6 have been achieved, extending further the possibility to address discrete properties in this series of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic helicenes, compounds that bear structural analogy to both triarylcarbenium ions and classical carbo or heterohelicenes, are strongly studied for their chemical and physical properties but also for their similarities to planar cationic triangulenes. These compounds 1 – 6 (Figure ), which exhibit classical helical screw-shaped skeletons formed by ortho -fused aromatic rings, are chiral and can be separated as single M or P enantiomers (left- and right-handedness) due to their high to very high configurational stabilities (Δ G ‡ 116.0–172.9 kJ·mol −1 and 124.8 to >155 kJ·mol −1 in [4] and [6]­helicene series, respectively). Not surprisingly, the barrier of racemization depends on the size of the helical core (the larger the better) and on the nature of the bridging heteroatoms, and this property is, of course, not the only one being controlled by the dioxa, , azaoxa, , or diaza ,, nature of the compounds . In fact, the modularity of the physical, electronic, and chemical properties of these [4] and [6]­helicenes , depends also on the heteroatoms, and this has led to many applications from biology ,, to physics as well as in analytical sciences and in (chir)­optical spectroscopy. , …”
Section: Introductionmentioning
confidence: 99%